1112 A Tertiary Neonatal Unit's Experiences in Establishing an In-House Cooling Service. (October 2012) - Broughton, R; Shaw, V; Borooah, M; Rasiah, SV
Abstract : Background: Hypoxic Ischaemic Encepalopathy (HIE) affects 1–2 per 1, 000 live births in UK. The TOBY study showed that therapeutic hypothermia (TH) is beneficial for babies with moderate HIE. In view of this we established an in-house cooling service. Aim: To review our experiences in establishing an in-house cooling service. Methods: The Badger electronic database was used to identify babies who received TH in the last 2 years (01/01/10 to 31/12/11). The management and outcomes were analysed. Results: In the last two year, 27 babies' commenced in-house TH. 3 babies were transferred out to another unit for TH for bed capacity reasons. A further 3 babies died before discharge home. 19 babies received the full 72 hours of cooling in our centre. We did not encounter any major complications with the servo-controlled cooling mattress. Only 50% of babies had their MRI in the defined time period as per the TOBY guidelines. All babies are being followed up by a dedicated consultant Neonatologist and neurodevelopmental physiotherapist to assess their neurodevelopment up to the age of 2 years. Conclusion: We have safely established an in-house cooling service by following the TOBY guidelines. The servo-controlled cooling mattress provides a safe cooling process with a rectal probe. Identifying these babies early and the interpretation of CFAM was an important aspect of training. Our main challenge was to get an MRI post cooling in a timely fashion. This has been resolved with an agreed dedicated slot for these babies at Birmingham Children's Hospital.